2017
DOI: 10.1007/s10714-017-2319-3
|View full text |Cite
|
Sign up to set email alerts
|

Information transfer during the universal gravitational decoherence

Abstract: Recently Pikovski et al. (Nat Phys 11:668, 2015) have proposed in an intriguing universal decoherence mechanism, suggesting that gravitation may play a conceptually important role in the quantum-to-classical transition, albeit vanishingly small in everyday situations. Here we analyze information transfer induced by this mechanism. We show that generically on short time-scales, gravitational decoherence leads to a redundant information encoding, which results in a form of objectivization of the center-of-mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Many different experiments have confirmed this principle [3][4][5][6][7][8][9][10], with the most stringent bound on its violations currently being a few parts in 10 −14 [9]. Recently, it was shown that the quantized gravitational interaction with composite systems yields novel effects and experiments [11][12][13][14][15][16][17][18][19][20][21][22][23][24], which rely on the coupling of gravity to the total energy of composite systems, as dictated by the equivalence principle.…”
Section: Introductionmentioning
confidence: 94%
“…Many different experiments have confirmed this principle [3][4][5][6][7][8][9][10], with the most stringent bound on its violations currently being a few parts in 10 −14 [9]. Recently, it was shown that the quantized gravitational interaction with composite systems yields novel effects and experiments [11][12][13][14][15][16][17][18][19][20][21][22][23][24], which rely on the coupling of gravity to the total energy of composite systems, as dictated by the equivalence principle.…”
Section: Introductionmentioning
confidence: 94%
“…The measurement Hamiltonian which is used to study the emergence of spectrum broadcast structure states is, in fact a special case of the general Hamiltonian which leads to pure dephasing evolutions [6][7][8][9][10][11][12][13] in a systemenvironment scenario [30,31]. The Hamiltonian is given byĤ…”
Section: Pure Dephasing Evolutions and Sbs Statesmentioning
confidence: 99%
“…To study situations when the emergence of objectivity is possible in the above sense of SBS creation, typically system-environment interactions are taken into account which lead to pure dephasing of the qubit [6][7][8][9][10][11][12][13] after the environmental degrees of freedom are traced out. These types of interactions describe situations when the T * 2 times are much shorter than the T 1 times (the decay of phase coherence is much faster than relaxation) are fairly common in solid state scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…II C, we investigate the asymptotic behaviour of the orthogonalization and decoherence processes in spin models using the Weak Law of Large Numbers (LLN). We develop some tools which are useful for the analysis of the quasi-periodic functions often occurring in similar models [1,3,5,30,31]. In sec.…”
Section: Introductionmentioning
confidence: 99%